Applying the Problem Behavior Theory to Adolescent Drug Use Among a Cross-Sectional Sample of Boys Participating in a Community-Based Youth Organization. (21st March 2018) - Alexander, Adam C.; Obong'o, Christopher O.; Chavan, Prachi; Vander Weg, Mark W.; Ward, Kenneth D.
ABSTRACT: Background: Drug use remains an important public health concern in the United States, and understanding drug use among young adolescents is vital towards improving the health of the population. Objective: This study applied the Problem Behavior Theory (PBT) to lifetime drug use among a cross-sectional sample of Boy Scouts ( N = 770). The PBT provides a conceptual framework for identifying risk and protective factors for adolescent problem behaviors, including drug use. Methods: Scouts reported their drug use and socio-demographics, and were assessed on several risk and protective factors. For analyses, sociodemographic and risk and protective factors were selected according to the framework provided by PBT, and use of each drug was regressed logistically on these selected factors. Final logistic models were assessed for goodness of fit and discriminatory power. Results: The PBT demonstrated discriminatory power for all drugs (Tjur's R 2 values ≥.29), but fell sharply for illicit drug use (Tjur's R 2 =.20). There were no consistent correlates of drug use. Conclusions/Importance: The PBT had less explanatory power for illicit drug use compared to tobacco, alcohol, and marijuana, which suggests different risk and protective factors were associated with illicit drug use.